2018
DOI: 10.1111/cei.13236
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of preterm gnotobiotic piglets with probioticLactobacillus rhamnosusGG and its interference withSalmonellaTyphimurium

Abstract: Summary A balanced microbiota of the gastrointestinal tract (GIT) is a prerequisite for a healthy host. The GIT microbiota in preterm infants is determined by the method of delivery and nutrition. Probiotics can improve the GIT microbiota balance and suitable animal models are required to verify their harmlessness. Preterm gnotobiotic piglets were colonized with Lactobacillus rhamnosus GG (LGG) to evaluate its safety and possible protective action against infection with an enteric pathogen, Salmonella Typhimur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 82 publications
(130 reference statements)
5
21
0
Order By: Relevance
“…It is known that pigs challenged by various pathogenic bacteria display diarrhea, growth retardation, and high fever [22,34,35]. In our study, we also found that piglets in TG exhibited diarrhea and body weight loss (Figure 1A,C), which suggested that C. perfringens type C and its fatal toxins could impair the integrity of the intestinal barrier and then caused diarrhea; persistent diarrhea then led to body weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…It is known that pigs challenged by various pathogenic bacteria display diarrhea, growth retardation, and high fever [22,34,35]. In our study, we also found that piglets in TG exhibited diarrhea and body weight loss (Figure 1A,C), which suggested that C. perfringens type C and its fatal toxins could impair the integrity of the intestinal barrier and then caused diarrhea; persistent diarrhea then led to body weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…Concordantly, IL-8 levels in plasma was found in the experiment with preterm less mature gnotobiotic piglets infected with S . Typhimurium [21]. Lower levels of plasma TNF-α compared with our previous results [58] were found.…”
Section: Discussionmentioning
confidence: 54%
“…Thirty evenly spaced radial lamina mucosalis propria widths per each piglet were measured. Histological scoring was evaluated as described elsewhere [21]. Briefly: i) Submucosal edema (0–2); ii) PMNs (polymorphonuclear neutrophils) infiltration into the lamina propria (0–2); iii) villus atrophy (0–3); iv) exudate in lumen (0–2); v) vessels dilatation (0–2); vi) inflammatory cellularity in lymphatic vessel lumen (0–2); vii) hyperemia (0–2); viii) hemorrhage (0–2); ix) peritonitis (0–1); or x) erosion of the epithelial layer (0–3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella Typhimurium strain LT2 is a well-characterized laboratory strain [58]. It was safe for one-week-old conventional piglets after its oral application [59], but it caused gastroenteritis and sepsis in immunocompromised germ-free piglets of the same age [60].…”
Section: Introductionmentioning
confidence: 99%